Associations of single and multiple vitamin exposure with childhood eczema: data from the national health and nutrition examination survey - Wang, Fang; Wang, Xiaolie; Wang, Jiayan; Liu, Biqing (Frontiers in Pediatrics, 2024)
Aim: Vitamins is closely related to eczema. Few studies have evaluated the effects of co-exposure to multiple vitamins on eczema. This study aimed to assess the association of vitamins mixtures on eczema in children.: This cross-sectional study collected the data of 2244 children aged 6-17 years from National Health and Nutrition Examination Surveys. Eczema was the primary outcome. Six serum vitamins, including vitamin A, vitamin B6, vitamin B12, vitamin C, vitamin D, and vitamin E were main variable. Weighted multivariate logistic regression was adopted to analyze the association between each serum vitamin and eczema. Odds ratio (OR) with 95% confidence interval (CI) were calculated. Using Bayesian Kernel Machine Regression (BKMR) analysis, and quantile g-computation (qgcomp) model, to evaluate the association of co-exposure to multiple vitamins with eczema.Results: In total, 10.83% children (n = 243) developed eczema. After adjusting for confounding factors, we observed that compared with the reference group (vitamin B12 with second quartile), the OR of eczema was 0.604 (95%CI: 0.373-0.978, P=0.041) for the first quartile of vitamin B12. Both BKMR analysis and qgcomp model consistently showed that co-exposure to six vitamins was positively correlated with the risk of eczema. where vitamin B6 contributed most to the overall effect. In BKMR analyses, we observed that there may be an interaction between vitamin B6 and vitamin B12 on eczema risk.Co-exposure to vitamin A, vitamin C, vitamin B6, vitamin B12, vitamin D and vitamin E was associated with an increased eczema in children, and vitamin B6 were the greatest positive contributors driving the overall effect.